(untitled) (Tempo e Argumento, 2024)
This article proposes a reflection on authoritarian permanence in the course of the Brazilian political transition, based on the analysis of discourses on the role of public security in social control. Guided by the theoretical-conceptual reflection of transition, authoritarianism and violence and understanding that during the civil-military dictatorship public security acted based on the National Security Doctrine, guided by the use of repression to control the internal enemy, we seek to understand the debates on the role of and logic of public security, within the scope of the Municipality of São Paulo. In order to do so, we will approach two segments of reflection, in an archegenealogical analysis: the first, related to the analysis of institutional practices, unraveling how Public Security was organized; the second, referring to the political clashes around public security, through the analysis of the speeches of the councilors of São Paulo, in the period of 1983-1986.